The synthesis of poly-4-thiouridylic acid and its effect on protein synthesis in a cell free system derived from rat liver - Hochberg, A.A. (1974)
The synthesis of poly-4-thiouridylic acid by thiolation of polycytidylic acid is described. A quantitative thiolation was achieved without any cleavage of the phosphodiester bond. The inhibitory effect of the poly-4-thiouridylic acid on protein synthesis in a cell free system derived from rat liver was investigated.